Evidence for a possible quantum effect on the formation of lithium-doped amorphous calcium phosphate from solution - Joshua S. Straub; Manisha L. Patel; Mesopotamia S. Nowotarski; Lokeswara Rao; Mark E. Turiansky; Matthew P. A. Fisher; Matthew E. Helgeson (Proceedings of the National Academy of Sciences, 2025)
Differential isotope effects are an emerging tool for discovering possible nontrivial quantum mechanical effects within biological systems. However, it is often nearly impossible to elucidate the exact mechanisms by which a biological isotope effect manifests due to the complexity of these systems. As such, one proposed in vitro system of study for a quantum isotope effect is calcium phosphate aggregation, where symmetric calcium phosphate molecular species, known as Posner molecules, have been theorized to have phosphorus nuclear spin–dependent self-binding rates, which could be differently modulated by doping with stable lithium isotopes. Here, we present in vitro evidence for such a differential lithium isotope effect on the formation and aggregation of amorphous calcium phosphate from solution under certain conditions. Experiments confirm that lithium incorporates into amorphous calcium phosphate, with 7 Li found to promote a greater abundance of observable calcium phosphate particles than 6 Li under identical solution preparations. These in vitro results offer a potential explanation for in vivo biological studies that have shown differential lithium isotope effects. Given the importance of calcium phosphate in biological systems—ranging from mitochondrial signaling pathways to key biomineralization processes, as well as the proposed role of Posner molecules as a “neural qutrit”—these results present an important step in understanding calcium phosphate nucleation as well as the potential role of calcium phosphate for quantum biology and processing.